Homework in the curricular area of mathematics in primary education - Lopes, Fabiana (2020)
The present study aims to identify the perspectives of pupils and their parents/guardians related to homework in the curricular area of mathematics and how they are implemented. A study was developed using a descriptive research, resorting to various techniques of data collection: a questionnaire for the pupils, an interview to the parents/guardians and documentary research of teachers' homework records. The study involved fifty students of two 4th grade classes of a Portuguese primary school, aged from 9 to 11 years old of both sexes, four parents/guardians of these students and two teachers. Homework is a widespread practice in both classes under study, being part of the daily life of pupils and their families. The type of homework most often requested in the area of Mathematics consists of worksheets that involve algorithmic calculation and some problem solving. Parents are actively involved in supporting their children’s homework, despite the difficulties they experience in such support. Homework represents a pedagogical strategy that is quite common, but seldom a target of reflection. It is important for teachers to reflect on the usefulness, type and extent of homework requested, as well as on student queries and parents’ difficulties in supporting its fulfilment, so that it can be a true complement to classroom learning for all pupils.